2018
DOI: 10.1186/s13046-018-0777-4
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint therapy in liver cancer

Abstract: Immune checkpoints include stimulatory and inhibitory checkpoint molecules. In recent years, inhibitory checkpoints, including cytotoxic T lymphocyte–associated antigen 4 (CTLA-4), programmed cell death protein-1 (PD-1), and programmed cell death ligand 1 (PD-L1), have been identified to suppress anti-tumor immune responses in solid tumors. Novel drugs targeting immune checkpoints have succeeded in cancer treatment. Specific PD-1 blockades were approved for treatment of melanoma in 2014 and for treatment of no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
215
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(220 citation statements)
references
References 85 publications
4
215
0
1
Order By: Relevance
“…Recent studies have confirmed that CSN signaling is important in cell cycle control, signal transduction, transcriptional activation, DNA repair, and tumorigenesis. 11,26,27 As an important subunit of the COP9 family, CSN5 could modulate PD-L1 stabilization in breast cancer cells. 20 Structurally, CSN6 and CSN5 form a heterodimer through the MPN domain, and the dimer is topologically knotted to engage in Cullin deneddylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed that CSN signaling is important in cell cycle control, signal transduction, transcriptional activation, DNA repair, and tumorigenesis. 11,26,27 As an important subunit of the COP9 family, CSN5 could modulate PD-L1 stabilization in breast cancer cells. 20 Structurally, CSN6 and CSN5 form a heterodimer through the MPN domain, and the dimer is topologically knotted to engage in Cullin deneddylation.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1/PD-L1 checkpoint blockades have positively changed the treatment patterns for advanced non-small cell lung cancer (NSCLC), renal cancer, chronic Hodgkin's lymphoma, gastric cancer, urothelial cancer, cervical cancer, head and neck squamous cell carcinoma, hepatocellular carcinoma, and melanoma. [10][11][12][13][14] The mechanisms of PD-L1 expression in cancer cells involve multiple levels, including gene amplification, chromatin modification, transcription, and posttranscription. [15][16][17][18][19] Oncogenic RAS signaling can upregulate PD-L1 expression through a mechanism involving messenger RNA (mRNA) stability.…”
mentioning
confidence: 99%
“…In recent years, immunotherapy has is supposed to be an attractive treatment investigated in liver maligancy. However, resistance to immune checkpoint blockades has been observed in most cancer patients [3,4]. Therefore, it is still urgently needed to develop novel strategies for the management of liver cancer.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently five anti-PD-1/PD-L1 antibodies and two CTLA-4 blocking antibodies approved by the United States Food and Drug Administration (FDA). But only Nivolumab and Tremelimumab were approved to treat with HCC, with clinical trials of ICI agents currently ongoing [25] . The overall estimated ORR is only 19.8% based on the current study, which needs to be verified with multicenter randomized controlled studies and clinical trials with other endpoints (such as overall survival, OS).…”
Section: Discussionmentioning
confidence: 99%